La Sozialdemokratie et la guerre : le crime des socialistes allemands : petit dossier documentaire - Destrée, Jules; Vandervelde, Emile; Gille, Paul; Laskine, Edmond (Paris : Richard Frères, 1915)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Wereldoorlog 1